1999
DOI: 10.1063/1.123384
|View full text |Cite
|
Sign up to set email alerts
|

Substitutional carbon incorporation in epitaxial Si1−yCy alloys on Si(001) grown by molecular beam epitaxy

Abstract: We show that C incorporation kinetics depend significantly on the carbon concentration. The carbon substitutionality (fraction of substitutional incorporated carbon atoms) is strongly influenced by the growth conditions, such as growth temperature and Si growth rate. In addition, reduction in the growth temperature and increase of the growth rate can both increase the substitutional carbon fraction. This behavior is well described by a kinetic model, with the energy barrier and preexponential frequency factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 65 publications
(32 citation statements)
references
References 9 publications
2
30
0
Order By: Relevance
“…In addition, fluctuations and defects hamper the propagation of dislocations which is also a cause of the inhomogeneity. Regarding the carbonrelated defects, it should be noted that substrate temperature also affects the substitutional to interstitial carbon concentration ratio [12,17] which possibly affects the formation of defects. For samples B and C, the top Si layers are distinguishable in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, fluctuations and defects hamper the propagation of dislocations which is also a cause of the inhomogeneity. Regarding the carbonrelated defects, it should be noted that substrate temperature also affects the substitutional to interstitial carbon concentration ratio [12,17] which possibly affects the formation of defects. For samples B and C, the top Si layers are distinguishable in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The separation between the partial dislocations depends also on the substrate temperature on which magnitude of the friction stress depends [37,38]. In addition, the substrate temperature affects the strain relaxation process via precipitation of carbon related complexes or b-SiC nanocrystals [17,39,40]. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A more likely explanation is the formation of non-stoichiometric Si-C interstitial complexes (which are different from stoichiometric SiC precipitates having a crystalline structure) or C clusters during the growth, acting as defect nucleating centers [17,28]. The formation of non-stoichiometric interstitial Si-C is also supported by the studies of Osten et al [17]. An increase in C concentration reduces the energy barrier to form many Si-C complexes in the lattice.…”
Section: Impact Of C Incorporation On the Materials Qualitymentioning
confidence: 88%
“…A couple of reports pertaining to the use of disilane to grow Si:C layers (in both gas-source Molecular Beam Epitaxy (MBE) as well as Chemical Vapor Deposition (CVD)), are already available [12][13][14][15][16][17][18][19]. Recently, Hartmann et al [19] have demonstrated a selective process for Si:C and Si:C:P deposition using disilane.…”
Section: Introductionmentioning
confidence: 96%